Vaginal birth after cesarean - Gupta, Shilpa; Ganatra, Hina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A heightened awareness must be present among the clinicians while taking the decision to perform the first cesarean section, as it decides the future obstetric career of the women. Because of the rise in cesarean section rate in recent decades, the question of how to manage the subsequent deliveries becomes important. Vaginal birth after cesarean (VBAC) has long been proposed as an alternative measure to reduce repeat cesarean rate. Our present study aims to assess the predictive factors of successful VBAC and study the risks and benefits involved. Methods: A prospective observational study was conducted to assess the success of VBAC and its outcome in GMERS Medical College and Hospital, Ahmedabad. A total of 100 pregnant women with history of previous one cesarean section who fulfilled the criteria for vaginal delivery were recruited for study and the outcome was analyzed. Results: The success rate of VBAC was 58% while failed TOLAC which ended up in emergency repeat cesarean section was 42%. Vaginal delivery either before or after the history of previous cesarean section, neonatal birth weight between 2.5-3kg, and admission during active phase of labour were associated with successful VBAC. There were 2 cases of partial scar rupture diagnosed peroperatively. The commonest indication of repeat cesarean section was non progress of labour (45.2%) followed by fetal distress (16.7%). The neonatal morbidity rate was similar in both groups due to limited prolonged unsuccessful trial in our study. There was no maternal and neonatal mortality. Conclusions: To reduce the escalating rate of total cesarean section worldwide, VBAC is an alternative option which should be encouraged in carefully selected patients. However, it should be carried out in a well equipped institute with close fetal monitoring and availability of blood and trained personnel. Thus “once a cesarean section, always a hospital delivery” and not, “once a cesarean section, always a cesarean section”.